Penerapan Metode Analytic Hierarchy Process Untuk Menentukan Kelayakan Jalan Beton dan Aspal di Garut - Abil Miftahul Mubarok; Ganjar Jojon Johari; Athaya Zhafirah (Jurnal Konstruksi, 2026)
This study analyzes the feasibility of using concrete and asphalt roads using the Analytic Hierarchy Process (AHP) method. Data were obtained from respondents’ assessments of technical, economic, and operational factors. The results show that concrete roads are superior in terms of resistance to weather conditions, ground movement, and traffic load variations, while asphalt roads perform better in surface comfort and ease of construction. The recommendations include considering initial costs, maintenance requirements, and environmental conditions in selecting the appropriate type of road. This research focuses on developing an AHP-based model to evaluate which road construction type, concrete or asphalt, has better overall feasibility. The AHP model development consists of three main steps: hierarchy construction, assessment, and priority synthesis. The assessment results for each factor indicate that, in terms of resistance to weather conditions, concrete is six times superior to asphalt; in resistance to ground movement, concrete is five times superior; and in resistance to traffic load changes, concrete is 5.5 times superior. In terms of surface comfort, asphalt is 5.5 times superior to concrete; in ease of construction, asphalt is five times superior; in maintenance period, concrete is five times superior; in resource availability, asphalt is three times superior; and in cost, asphalt is twice as economical as concrete. The final assessment based on weighting, as reflected in the VA21 vector, indicates that asphalt construction is slightly more feasible than concrete construction, as shown by the higher eigenvalue for asphalt (0.529) compared to concrete (0.472).